Sundial Dalam Sejarah Dan Konsep Aplikasinya - Elly Uzlifatul Jannah; Elva Imeldatur Rohmah (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2019)
Sundial is a device used as a hint of local pseudo-time using the sun, thus producing the shadows of the gnomon. Sundial is the oldest hour and was first used around 3500 BCE. Sundial consists of several types, namely horizontal, vertical, and equatorial Sundial. Each sundial has its own rules in its creation and the concept of its application. The working principle of this clock is by showing the location based on the sun by looking at the shadows of the sun. As one of the timepiece tools, the sundial not only serves as a tool to know the timing only. It has several other functions, such as the season determinant and the direction of Qibla. However, the entire function of the sundial can only function with the help of the sun as its appointment. By application and the theory, sundial has an excess compared to the math clock. This is because the routine of worship and human social activity is absolutely determined by the time of the Sun standard, not the clock. Because the clock is just the average calculation of the sun's circulation averages around the earth, so the clock can not show the actual time. The sundial can also be used as a time-to-date verifier, as well as a prayer time guideline without time correction, such as digital clock or analog clock.